Oxysterol-Induced Inflammation in Human Diseases: Strategies for Treatment with Natural Compounds and Synthetic Molecules - Fatiha Brahmi; John J. Mackrill; Imen Ghzaiel; Leila Rezig; Rym Benkhalifa; Amira Zarrouk; Pierre Jouanny; Anne Vejux; Gérard Lizard (Molecules, 2025)
Oxysterols can be derived from the diet, physiologically produced via specific enzymes, or are generated by autoxidation. These molecules have physiological properties and can also adversely affect vital organs. Indeed, some of them have pro-oxidant and pro-inflammatory activities and can lead to major pathologies. The present review focuses on oxysterols (7-ketocholesterol, 7β-hydroxycholesterol, 25-hydroxycholesterol, 27-hydroxycholesterol, 5,6α-epoxycholesterol, 5,6β-epoxycholesterol, and cholestane-3β, 5α, 6β-triol) involved either in cholesterol metabolism, age-related diseases (such as cardiovascular, neurodegenerative, and eye diseases, e.g., sarcopenia), and inflammatory diseases (especially Behcet’s disease and bowel and lung diseases (e.g., sarcoidosis, COVID-19)). Metabolic pathways associated with oxysterol-induced inflammation are discussed considering the cytokinic TLR4 pathway, non-cytokinic pathways, and the contribution of Ca2+ and K+ channels. Therapeutic approaches targeting oxysterol-induced inflammation either by natural or synthetic molecules are also presented.